Global and regional shocks: Challenges to Asian economies - Kwanho Shin (Asian Development Bank Institute (ADBI), 2008)
Two major economic problems are currently shadowing Asian economies. On the one hand, the slowdown in the US economy, ignited by the subprime mortgage crisis, may not be confined to the US region and may affect Asian countries as well. On the other hand, the recent fuel and food price increases, a global shock in nature, are also likely to influence most Asian economies that are heavily dependent on oil imports. In this short article, by summarizing recent studies on these issues, I address how Asian economies in particular are challenged by these important developments in the world economy. I also identify policy issues faced by the policymakers in Asia. Recent studies show that East Asia is quite integrated in trade. Financial integration has also progressed, but the extent of financial integration is not as remarkable as trade integration has been in the region. By contrast, East Asian countries' financial links to the global center (i.e., the US market) are quite strong. These studies have also shown that trade integration greatly enhances business cycle co-movements of output. There is also evidence that financial integration also leads to more co-movements of output, but its impact is relatively weak. Hence, the deepening trade integration in East Asia indicates that the impact of slowdown in the US economy is not likely to be large. Since the impact of financial integration is not large, the fact that most Asian countries' financial markets have strong ties with the US financial market does not necessarily dispute this prediction. However, since most studies are based on non-crisis periods, there is a possibility that the financial crisis that originated in the US, if it is very severe, may generate a much larger influence on Asian countries. On the other hand, the recent fuel price increases are of a more global nature. Most Asian countries, still heavily dependent on the manufacturing sector, are expected to be more adversely affected by the oil price increases than advanced countries will be. If these increases continue, the central banks of Asian countries will face a dilemma of high inflation or economic slowdown. Of particular interest is that this will be the first serious challenge for many emerging Asian countries that have adopted inflation targeting.
Keywords: E52; E66; E42; 330